The effectiveness of using video to teach how to write a procedure text during the pandemic era - Qurrota A'yun (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACTKey words: Video, Procedure text, writingWriting is one of English skill that must be mastered by the students. In this online learning, the writer utilizes video as the learning method to teach the students by demonstrating something in good explanation. In this case, the method was used to make the students easy to understand about writing procedure text especially in this pandemic era of COVID-19. The research design in this study was used quantitative research design, true experimental design. There were 60 students in the ninth grade and divided into two groups, experimental and control group where each group were consist of 30 students. The treatment that was given to the experimental group was using a video which consisted of explanation of procedure text, an action of procedure text, and the way to write procedure text which was taught at the fourth meeting by using WhatsApp Group while control group was given the same material in the form of textbook. Then, the writer provided to the students to make a paragraph of procedure text to measure the students’ achievement.To analyze the data, the writer used SPSS 20 that was Independent T-test. The result showed the mean of experimental group was (M= 82.13) and the control group was (M= 77.06). At the same time it was shown the p value was 0.000 (p < 0.05). After knowing the result of the data, it indicated that using video to learn procedure text was more effective to be implemented by the students in this online learning.